Management of Local Wisdom Based Curriculum Development at MDT Nurul Huda Magelang - Islamiyah Nur Hidayati; Farida Inayati Tsania; Purnomo (LPPM Universitas Ibn Khaldun, Bogor, 2025)
This study aims to analyze the management strategies of curriculum development based on local wisdom at Pondok Pesantren Nurul Huda Magelang, focusing on the formulation, implementation, and evaluation mechanisms of the curriculum. Employing a post-positivist qualitative approach, data were collected through observation, interviews with key institutional figures, and document analysis. The study found that the curriculum development at MDT Nurul Huda Magelang was formulated in alignment with national regulations and local needs through a SWOT analysis. Curriculum implementation was carried out through three approaches: strengthening core Islamic teachings within a local context, internalizing values through local traditions, and developing skills rooted in cultural practices. Curriculum evaluation was conducted comprehensively and participatively, resulting in graduates who not only master religious sciences but also embody the character of rahmatan lil ‘alamin—civilized, moderate, and nationally minded individuals. This study contributes to the development of Islamic Religious Education curricula that are more relevant to the needs of students and society. The findings of this research can serve as a reference in designing MDT curricula that instill Islamic character values.